Pengaruh Penggunaan Metode Pembelajaran Contextual Teaching and Learning, Cooperative Learning, dan Gaya Berpikir Siswa terhadap Kemampuan Memahami Konsep Mata Pelajaran PPKn Siswa Kelas VIII di SMP Negeri 57 dan 49 Surabaya - Djelita, Ruti Diah Puspita; Fatirul, Achmad Noor; Wiyarno, Yoso (LP. Ma'arif Janggan Magetan, 2023)
This study focuses on the existence of significant differences in the ability to understand concepts between students who are taught by contextual teaching and learning and cooperative learning methods, there are significant differences in the ability to understand concepts between students who have a concrete sequential thinking style, abstract sequential, concrete random, and abstract randomization, as well as the interaction between learning methods and thinking styles on the ability to understand the concepts of Civics subjects for class VIII students at SMP Negeri 57 and 49 Surabaya. This type of research is experimental research. Quasi-experimental research design using a non-equivalent control group design. The population of this study were class VIII students of SMP Negeri 57 and 49 Surabaya for the 2022/2023 academic year. The research sample used a sampling technique with details of 72 students in the experimental class and 70 students in the control class. The data collection method is to use a student thinking style test instrument and a test of the ability to understand